A REVIEW OF NUTRIENT DEFICIENCIES AMONG PEOPLE WITH OBESITY: ITS IMPLICATION ON THE USE OF THE TERM OVERNUTRITION IN INDONESIA - Fikri, Al Mukhlas; Harianti, Rini; Sudikno (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Obesity is a global pandemic that is closely related to the emergence of non-communicable diseases and premature death. Although obesity results from excess energy intake, deficiency of other nutrients are commonly found. Therefore, the use of the term overnutrition to describe obesity creates misperceptions. The objective of this review was to provide the evidence of a nutritional deficiency condition in obesity that can be used as a basis for considering the use of the term in Indonesia. The review was performed with unstructured literature search on several databases, such as PubMed, Scopus, ScienceDirect, and Google Scholar. Although obesity is caused by excess intake of macronutrients, the results of this review showed that many studies reported micronutrient deficiencies were present in people with obesity. The deficiencies were commonly reported, including deficiency of vitamin D, vitamin B12, folate, iron, calcium, and phosphor. The main causes were the habit of consuming food with a high content of macronutrients, but low in micronutrients, and metabolic consequences of body fat accumulation. Moreover, the deficiencies of micronutrients contributed to an increased risk of diseases, such as diabetes, cardiovascular disease and cancer. Meanwhile, the Global Nutrition Report has not used the term overnutrition, instead to use overweight and obesity. Therefore, the use of the term in Indonesia to describe obesity needs to be further reviewed. However as this is a narrative review, more comprehensive and systematic review is still needed.